Pemberdayaan Masyarakat Melalui Pengolahan Singkong Mentega Menjadi Kerupuk Rengginang di Kabupaten Kubu Raya - Arni, Arni; Fitriani, Fitriani; Simarmata , Mai Yuliastri; Agustina , Rini; Mastuti , Dewi Leni (Civiliza Publishing, 2024)
This article is the result of Community Service (PKM) in Banjar Sari Hamlet, Rasau Jaya Dua Village. Rt 003.Rw 02. The PKM activities carried out are part of community empowerment to increase family income through training on processing cassava into rengginang crackers and training on productive business management to increase income for local mothers. The results of PKM activities through this training are rengginang cracker products as a business that can help housewives improve the family economy. This PKM activity lasts for three days involving partners who are professional and experienced in processing cassava into ready-to-sell rengginan crackers. This training is a real form of community service that makes a positive contribution so that it can improve the economic level of the community.